Pengaruh Label Halal, E-WoM, FoMO, dan Brand Trust Terhadap Keputusan Pembelian Produk Skincare Halal - Erika Dewi Ari Mita; Ach. Yasin (Universitas Negeri Surabaya, 2024)
This research aims to determine and analyze the effect of halal labels, E-WoM, and FoMO on purchasing decisions for halal skincare products with brand trust as a moderating variable in Muslim communities in Tuban Regency. The research method is applied through a quantitative approach, with primary data collection through questionnaires distributed online in the form of Google forms. Sampling was carried out through purposive sampling technique with the criteria that respondents were people in Tuban Regency who were Muslim, aged 18 to 30 years, had bought and used halal skincare. The results of this study indicate that halal labeling, E-WoM, and brand trust have a significant influence on halal skincare purchasing decisions, while FoMO has no significant effect on halal skincare purchasing decisions. This shows that the Muslim community in Tuban Regency does not experience FoMO regarding halal skincare, but when making decisions to purchase halal skincare Muslim communities in Tuban Regency consider the halal label, E-WoM, and also brand trust.